The Relationship between Nursing Students’ educational Satisfaction and their academic success - Mitra Edraki; masoumeh rambod; Rouholah Abdoli (مجله ایرانی آموزش در علوم پزشکی, 2011)
Introduction: Students’ educational satisfaction has been identified as an indicator of the quality of the students’ learning and educational system. It may also affect academic success among students. The aim of this study was to determine the relationship between nursing students' educational satisfaction and their academic success. Methods: It was a descriptive co-relational study. One hundred seventeen nursing students in Nursing & Midwifery school of Shiraz University of Medical Sciences, selected by convenience sampling method, participated in the study during school year of 2006-2007 . The data were collected by education satisfaction standardized questionnaire. Academic success was determined by students’ Grade Point Average (GPA). Data were analyzed by chi-square test, independent T–test and ANOVA. Results: The findings of this study showed that there is a relationship between students' educational satisfaction and their academic success (t= 114.22, p<0.0001). In addition , educational satisfaction among the subjects was in a moderate level (56.4%). Statistical analysis indicated that there was a significant difference between the educational satisfaction and academic success and various students ‘ university entrance year . In addition, there was an association between students’ grade point average and their gender. Conclusion: This study indicated that there is an association between nursing students’ educational satisfaction and their academic success. Therefore, Students’ educational satisfaction can be an indicator of the quality of learning and academic achievement in nursing students.